Development of a risk map, a risk allocation matrix, and a risk assessment matrix for the energy construction sector - Więcław-Bator, Lidia; Chmielewski, Ryszard; Kruszka, Leopold (Archives of Civil Engineering, 2026)
This article presents an integrated framework for developing risk management tools tailored to energy construction projects. It advocates for a transition from traditional reactive methods toward a proactive, engineering-led approach. The study examines the systematic development and synergistic application of three distinct tools: risk maps, risk allocation matrices, and risk assessment matrices, evaluating their collective impact on key project parameters such as cost, schedule, scope, and quality. Central to the research is a multi-dimensional analysis of sector-specific risk determinants, ranging from macroeconomic volatility and regulatory shifts to the complex technical interdependencies inherent in high-voltage infrastructure. Grounded in the contractual frameworks of the “Code of Good Practices for the Energy Industry” (PZPB) and “Standards for Investment Execution” (SIDiR), and bolstered by empirical research conducted between 2022-2025 regarding contractor claims in 35 national electric power projects, the article develops practical, validated tools for comprehensive risk management.